A Cultural Approach To The Interaction Of Culture And War And Its Impact On Socio-Cultural Processes In Ukraine - Bukhnieva, Olena (Journal of Danubian Studies and Research, 2023)
The article analyzes the content of state cultural policy, outlines its goals and objectives, which are determined by socio-economic, political, historical and other features of the development of Ukrainian society. The article examines the relevance of modern problems in the parameters of the interaction of culture and war. In the conditions of the introduction of innovative technologies in all spheres of human life, including the military, this problem has become especially important for the fate of all people of the earth. It has been proven that along with the philosophical and sociological approach, cultural analysis plays a significant role in revealing the actual issues of the essence, causes, nature and role of wars, the regularities of their course and outcome. Cultural studies, acting as the methodological basis of research, allows for a deeper understanding of social life and the phenomena that occur in it.